The Effect of Leadership Style and Competence on Performance With Job Satisfaction as an Intervening Variable - KAWISANA, Putu Gede Wisnu Permana; NARINDRA, A.A Ngurah Mayun; DHARMANEGARA, Ida Bagus Agung (PT Keberlanjutan Strategis Indonesia, 2023)
Throughout human civilization's history, it has been known that the dynamics and movements of an organization, to some extent, depend on humans as the implementers in carrying out organizational activities. When examined in general, the success of an organization or a company in achieving its goals depends on the components within the organization itself, such as leadership, employees, programs, objectives, facilities, and infrastructure available. Performance is crucial in a company because it is closely related to the activities carried out by employees. Mangkunegara (2010) defines employee performance as the quality and quantity of work an employee achieves in carrying out their tasks by their responsibilities. Competence is a fundamental characteristic of an individual that influences how they think and act, make generalizations about all situations they encounter, and endure within a person for a considerable period (Ruky, 2006). Leadership style has a strong positive influence on Performance. In an institution, organizational behavior factors also directly or indirectly affect Performance. This study focuses on all SMEs (Small and Medium-sized Enterprises) near Badung Regency, using random sampling for testing variables with Smart PLS 4.0. From the research results, leadership style does not significantly influence employee performance; competence has a significant positive relationship with employee performance. Job satisfaction does not have a significant influence on employee performance. Leadership style does not have an indirect influence on employee performance. Competence does not indirectly influence employee performance through job satisfaction.